The development of a South African Early Learning Outcomes Measure: A South African instrument for measuring early learning program outcomes. (20th February 2019) - Snelling, Matthew; Dawes, Andrew; Biersteker, Linda; Girdwood, Elizabeth; Tredoux, Colin
Abstract: Background: Assessment of early childhood development programme effectiveness in South Africa is hampered by a lack of suitable measures that account for variations in cultural and socio‐economic backgrounds and can be administered by non‐professionals. This contribution reports the standardisation of the South African Early Learning Outcomes Measure (ELOM), an instrument designed for population level monitoring of the developmental status of children aged 50–69 months and for evaluation of early learning programmes. Methods: The development of the ELOM was informed by South Africa's National Curriculum Framework from Birth to Four and its National Early Learning and Development Standards. ELOM items were drawn from reliable and valid instruments, particularly those used in Africa and other developing regions and were clustered in five domains: gross motor development, fine motor coordination and visual motor integration, emergent numeracy and mathematics, cognition and executive functioning, emergent literacy and language. The ELOM was standardised on a sample of 1, 331 children aged 50–69 months, from five South African official languages and five socio‐economic strata. Item Response Theory techniques were used to establish reliability, validity, and differential item functioning. Results: Confirmatory Factor Analysis established that ELOM domains are unidimensional and internally consistent. Items discriminate reliably between more and less able children and do not discriminate unfairly between children of the same ability from different language backgrounds. Socio‐economic gradients were evident in children's performance. South African Early Learning Development Standards (ELDS) based on standard scores were developed and set at the 60th percentile of the sample standard score distribution. Conclusions: This research produced the first South African, age‐validated population‐level standardised instrument that can be administered relatively cheaply by trained non‐professionals. This will facilitate the assessment of the efficacy of early learning programmes in enabling children to reach ELDS prior to entering Grade R and track progress toward Sustainable Development Goal 4.2.